Dehydrogenative Meyer-Schuster-like rearrangement: a gold-catalyzed reaction generating an alkyne - Yu, Yang; Yang, Weibo; Pflästerer, Daniel; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2014)
Easily accessible propargylic esters are converted to the inverted alkynyl ketones in an oxidative gold-catalyzed reaction. Gagosz’s catalyst in combination with PhI(OAc)2 is the best system for this conversion and 18 examples with yields up to 80 % are reported. The results indicate that the triple bond in the product is formed by elimination from a vinylgold intermediate. In a formal sense the new conversion overall is a dehydrogenative Meyer-Schuster rearrangement.